Chemical composition of mesocarp and exocarp from Borassus flabellifer - M. H., Rodiah; Bakar, Jamilah; Abdul Rahman, Russly; Syed Muhammad, Sharifah Kharidah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Palmyra palm (Borassus flabellifer L.) belonging to the family Palmae has been reported to be the source of fiber, medicinal, food and beverage. The immature, soft, juicy seed nuts are popularly prepared as natural drink, but approximately 40-55% of the skins (mesocarp and exocarp) are discarded. Negligible literature is available on the composition of these parts of the fruit. Hence, the chemical composition of the mesocarp and exocarp from Borassus flabellifer were determined with the objective of evaluating the potential of utilizing these two fruit components into a value-added product. Proximate, total phenolic content and antioxidant activity analysis were carried out for both mesocarp and exocarp. Both mesocarp and exocarp had high crude fiber (23.92% and 28.20%, respectively) but low in ash, protein and fat contents. The carbohydrate content of all samples exhibited moderate amount of carbohydrate ranging from ~53 to 56%. Phenol and tannins were present in both mesocarp (5.58 mg GAE/g and 3.23 mg GAE/g, respectively) and exocarp (0.007 mg TAE/g and 0.003 mg TAE/g, respectively). Nevertheless, saponin was only detected in mesocarp at 16.75%. Alkaloids, cardiac glycosides, flavonoids, steroids, terpenoids and anthraquinone were not detected. Radical scavenging activity (157.05 mM TE/g) and reducing power (213.05 mM Fe2+) of exocarp were significantly higher (p< 0.05) than mesocarp. On the overall, this study indicates the present of significant amount of fiber and antioxidative properties in the mesocarp and exocarp of Borassus flabel lifer which could be a potential source as a functional ingredient.